Signaling Mechanisms by Arabidopsis Cryptochromes - Ponnu, Jathish; Hoecker, Ute (Frontiers in Plant Science, 2022)
Cryptochromes (CRYs) are blue light photoreceptors that regulate growth, development, and metabolism in plants. In Arabidopsis thaliana, CRY1 and CRY2 possess partially redundant and overlapping functions. Upon exposure to blue light, the monomeric inactive CRYs undergo phosphorylation and oligomerization, which are crucial to CRY function. Both the N and C terminal domains of CRYs participate in light-induced interaction with multiple signaling proteins. These include the COP1/SPA E3 ubiquitin ligase, several transcription factors, hormone signalling intermediates and proteins involved in chromatin-remodeling and RNA N6 adenosine methylation. In this review, we discuss the mechanisms of Arabidopsis CRY signaling in photomorphogenesis and the recent breakthroughs in Arabidopsis CRY research.